Electrochemical behaviour of haemoglobin at the liquid/liquid interface - Herzog, G.; KAM, V.; Arrigan, Damien (Pergamon, 2008)
The electrochemical behaviour of haemoglobin (Hb) at the liquid/liquid interface was investigated. Basedon ion transfer cyclic voltammetry and bulk ionolysis experiments, it is proposed that Hb adsorbs at theliquid/liquid interface and forms a multi-layer deposit thereafter repetitive cycling. However Hb does notcross the interface. The transfer peak current measured increased non-linearly with the bulk concentration of Hb in the aqueous phase but it did vary linearly with the square root of the scan rate. This diffusioncontrolled process is ascribed to the Hb-facilitated transfer of the anion of the organic phase electrolyte.The electrochemical signal also increases with time suggesting a conformational re-arrangement of Hbat the liquid/liquid interface. The transfer peak potential was seen to vary with the nature of the anion,in agreement with the trend in hydrophobicity of the anions examined. Furthermore, at pH values =pI ofHb, no transfer peak was observed, suggesting that neutral or negatively charged Hb does not facilitatethe transfer process.